Impact of environmental interventions based on social programs on physical activity levels: A systematic review - Hernández, Edgar D.; Cobo, Elisa A.; Cahalin, Lawrence P.; Seron, Pamela (Frontiers in Public Health, 2023)
Background. The design of social programs at the environmental level like schools, parks, bicycle paths, or workspaces generates changes in the behavior of individuals by modifying lifestyles by increasing physical activity levels OBJECTIVE. To determine the effectiveness of environmental interventions based on social programs by changing the level of physical activity in the population. METHODOLOGY. Natural experiment studies that involved environmental intervention programs at the social level were included. The primary outcome was physical activity levels with consideration of both objective and subjective measurements. An electronic search was carried out in Medline/Pubmed, SCIENCE DIRECT, WEB OF SCIENCE, and CINAHL databases up to January 2022, two reviewers screened titles and abstracts and selected studies by full-text reading. Relevant data and quality of studies evaluation by ROBINS I tool were performed by two reviewers as well. A qualitative analysis was considered. RESULTS. 3865 articles were found in the 4 consulted databases. After eliminating duplication (200), two reviewers screened 3665 titles and abstracts, and excluded 3566 because they did not meet the inclusion criteria, leaving 99 articles to be read in full text. The 99 full texts were reviewed of which 28 reports in 24 papers met the eligibility criteria. All were natural experiments published between 2011 and 2020, with the evaluation of environmental social programs from different parts of the world which revealed that social programs at the environmental level focused on the promotion of PA in the populations at the community level to improve physical activity. CONCLUSION The 24 experiments suggest innovative proposals for social programs that seek to increase activity and promote healthy lifestyles related to public activity policies developed in the countries in which they are generated. Having this type of environmental social programs can have a positive impact on the levels and practice of physical activity among children and adults.